Praktik Manajemen Strategi Dalam Membangun Kontinuitas Usaha UMKM: Analisis “Rantai Tak Putus” Karya Dee Lestari - Londo, Caroline Viona; Sesilia, Deselva; Kurniawan, Eva Dwi (Populer: Jurnal Penelitian Mahasiswa, 2024)
Micro, Small and Medium Enterprises (MSMEs) have a vital role in the Indonesian economy, creating new jobs, innovation and unique strategies. The growth phenomenon of MSMEs presents challenges and opportunities, encouraging the need for targeted strategies, in-depth market understanding and adaptability. This research explores strategic management practices in MSMEs in Dee Lestari's "Rantai Tak Putus". The strategies implemented include internal development, making the right decisions, and consistency in implementing positive values. The MSME players in this book are able to adapt strategic management to their business needs, not only for immediate business growth, but also to build a solid foundation for long-term sustainability. This creates an environment that supports business growth, strengthens competitiveness, and ensures the adaptability of MSMEs to change for sustainable business continuity.